ANALISIS STRATEGI BISNIS FRANCHISE MIXUE DALAM MEMPERLUAS PASAR DI INDONESIA MELALUI HARGA DAN MEDIA SOSIAL - Mai Sarah Nabila Putri (MANTRA (Jurnal Manajemen Strategis), 2026)
This study aims to analyze Mixue's business strategy in expanding its market in Indonesia. A descriptive qualitative approach was used, utilizing secondary data obtained from journals, books, articles, news sources, and social media. The results show that affordable pricing and effective social media marketing play a crucial role in attracting consumers, increasing brand awareness, and strengthening competitiveness. Supported by a strategic location, strong branding, and a franchise system, Mixue has successfully expanded its presence and achieved rapid growth in the Indonesian beverage market. Keywords : Mixue, business strategy, pricing strategy, social media marketing.